2014
DOI: 10.1007/s13277-014-1677-7
|View full text |Cite
|
Sign up to set email alerts
|

Propofol induces endoplasmic reticulum (ER) stress and apoptosis in lung cancer cell H460

Abstract: Propofol is one of the most commonly used intravenous anesthetic agents during cancer resection surgery. It can influence proliferation, motility, and invasiveness of cancer cells in vitro and in vivo. However, the role of the propofol in the lung cancer cells remains unclear. In this study, we demonstrated the effects of propofol on the proliferation and the apoptosis of lung cancer cell H460 by using colony formation assay and flow cytometry. Propofol also decreased tumor size and weight in established xenog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 16 publications
2
42
0
Order By: Relevance
“…Caspase-3 is a cysteine protease, which are pro-apoptotic proteins with prominent roles in ERS-induced cell death [42, 43]. ERS is well-characterized in human LC [44, 45]. Recent evidence has suggested that ERS can initiate internal pathways that may induce cellular death [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase-3 is a cysteine protease, which are pro-apoptotic proteins with prominent roles in ERS-induced cell death [42, 43]. ERS is well-characterized in human LC [44, 45]. Recent evidence has suggested that ERS can initiate internal pathways that may induce cellular death [27].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium imbalance or aberrant protein folding in the ER result in ERS and induce cell destruction responses [47, 48]. Alterations in the ER molecular chaperone levels can suppress tumor growth in vivo [44]. Likewise, ERS-induced apoptosis is also highly dependent on the upregulation of CHOP [49].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study revealed that propofol could inhibit cancer growth and invasion through Wnt/β‐catenin pathway . Through inducing endoplasmic reticulum stress, propofol increased cell apoptosis in lung cancer . Moreover, propofol could also suppress the pancreatic cancer proliferation and invasion via microRNA‐133a .…”
Section: Discussionmentioning
confidence: 99%
“…11 Through inducing endoplasmic reticulum stress, propofol increased cell apoptosis in lung cancer. 13 Moreover, propofol could also suppress the pancreatic cancer proliferation and invasion via microRNA-133a. 14 Besides, propofol has also been reported to inhibit the colon cancer invasion, via downregulation of MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation